THE OPTIMASI KAPASITAS WHEEL SHOP BERDASARKAN MAN POWER dan TOOLS DI PT XYZ MENGGUNAKAN LINEAR PROGRAMMING - Gunawan, Fathiqun Miftahul Zanna; Erna Shevilia Agustian; Ade Julizar (FTK UNSURYA, 2024)
As the airline industry continues to grow, it is important for airline companies to ensure operational efficiency in aircraft maintenance and repair. In this study, increasing production efficiency and management of Human Resources (HR) and tools related to time management, increasing the use of tools and the availability of man power. This study aims to analyze the Wheel Shop capacity optimization based on Man Power and Tools using the Linear Programming (LP) Method at PT XYZ. The Linear Programming (LP) method is used to design optimal solutions that take into account the availability of Man Power and Tools. The necessary data, such as the number of man power, working hours and the availability of tools, are collected, analyzed and the use of tools by optimizing capacity and designing the Linear Programming (LP) method in a simplex model. This research provides a comprehensive view of how Linear Programming can be applied to optimize Wheel Shop capacity based on Man Power and Tools, providing significant benefits in managing resources efficiently and optimizing the use of tools. optimization results on Wheel Shop capacity at PT XYZ that for the Zmax value get a result value of 2304, Man power with an optimum result value of 72, Time with an optimum result value of 24 and Tools with a result value of 192. In the calculation of this final project on Wheel Shop capacity optimization using the Linear Programming method with a simplex model that for calculations only up to Iteration 1 using Microsoft Excel Software because it immediately obtained the results of the Zmax value line all positive values